Benchmarking sustainability using indicators: An Indian case study. (February 2016) - Kwatra, Swati; Kumar, Archna; Sharma, Prateek; Sharma, Sumit; Singhal, Shaleen
Highlights: A sustainability index based on the broad themes of social, economy and environment. Comparison of Indian administrative regions on sustainability scale. Indian States follow Kuznet curves-show correlation between income and sustainability. Smaller administrative areas are better managed and show better indices. Abstract: This paper develops an index to measure sustainability based on the broad themes of social, economy and environment. Nineteen appropriate indicators were selected based on relevance, data availability, and periodicity for each leg of sustainable development. A correlation analysis was carried out to assess relationships between the 19 indicators representing different parameters under the three themes. These parameters were then normalized using Z -score technique. The Z -scores computed for each of these parameters were then used to develop a Sustainable Development Index (SDI). The index is pilot tested on different States and Union Territories (UTs) of India. The values are compared and interpreted to adjudge the forerunners and laggards on the various dimensions of human well-being and environment. Significant relationships have been observed between income levels and area of administrative regions with sustainability indices of the regions. Smaller administrative regions with higher income levels have been observed with higher sustainability scores. The proposed index provides a useful measure of identifying problematic areas that can be plugged through policy measures and ensures that the region moves on sustainable development pathways.